Wspomaganie osób starszych w ich miejscu zamieszkania - Dziendziura, Małgorzata (Pedagogika Społeczna Nova, 2026)
The subject of discussion in this article will be older adults and their support in their place of residence. Old age brings new challenges related to a reduced reservoir of psycho-physical strength and capabilities, as well as changes occurring in social and family life. Older adults often have to face health and financial difficulties, frequently with mobility limitations, which significantly affect their quality of life. Depending on their place of residence, they can benefit from support provided through neighborhood solidarity, the activities of non-governmental organizations, and the state, which, through its senior policy, offers assistance to older people in the form of financial, service-based, material, and institutional support. The living environment is a source of security, certainty, and an element of identity for older adults. However, with the passage of years, it must skillfully respond to their needs and the changes occurring over time related to lifestyle and health.